On the Implementation of Interdisciplinary Relationships in Classes in Chemistry with Disciplines of the Professional Cycle - Daminova Gulruh Bahromovna (Genius Journals, 2023)
This article describes the methodology and tasks of developing the structure of practical and experimental classes in chemistry based on interdisciplinarity
Keywords: interdisciplinarity; systematization; integration